ARBUSCULAR MYCORRHIZAL FUNGI: COMPOSITION, LENGHT EXTRARADICAL MYCELIUM AND GLOMALIN IN AREAS OF ATLANTIC FOREST, RIO DE JANEIRO - Silva, Cristiane Figueira da (2016)
The Atlantic Forest is considered an environment of great biodiversity. However, by constantly being subjected to intense human pressure, is very fragmented and disconnected, surrounded by extensive matrices formed by pastures, capoeiras, monocultures and urban areas. Fragmentation, as well as certain uses and soil management can cause changes in the composition and activity of soil microorganisms, such as mycorrhizal fungi (AMF). Fragmentation, as well as certain uses and soil management may entail a reduction of edaphic microflora. Thus, the study aimed to evaluate the composition of the population of mycorrhizal fungi (MF) in different areas, to determine the influence of vegetation on the abundance of AMF spores in the length of extraradical mycelium (LEM) and levels of Glomalin-related soil protein (GRSP) the ground. The systems were evaluated: annual crops (Anag); perennial agriculture (PAG), pasture, secondary forest early stage (SFES), secondary forest medium stage (SFME); advanced stage secondary forest (ASSF). Soil samples were collected at a depth of 0-5 cm, in two different seasons (summer and winter), and analyzed the abundance of spores and species composition of AMF, the LEM, and the presence of GRSP. It was recovered a total of 27 morphotypes of spores of AMF, and AMF species was that which was present in all areas studied in both seasons and in most cases with a high frequency of occurrence. The abundance of AMF spores was influenced by the type of vegetation. A low AMF sporulation was observed in the area of Anag both stations. The agricultural areas have changed the species composition of AMF in relation to forest systems. The concentration of GRSP - easily extractable (GRSP-EE) fell in the SFME for agriculture.